Eine Konjekur zu Catull. 64.260 - Ullrich, Heiko (Classica et Mediaevalia, 2026)
An emendation is offered on the text of Catull. 64.260, where audire seems inappropriate to describe the sensation of sacred objects hidden in a cista: pars obscura cauis celebrabant orgia cistis, / orgia quae frustra cupiunt †audire† profani (259-60). Despite the efforts of Friedrich, Schuddeboom and Trimble (following Kroll) defending audire seems impossible. The text can be improved dramatically by either McKie’s aperire or Oakley’s spectare which provide an (albeit not too) smooth transition from orgia meaning ‘sacred objects’ to orgia meaning ‘sacred rites’ (performed by using the sacred objects). Nevertheless, both conjectures can – and need to be – improved themselves: aperire goes beyond the requested meaning hinting at the divulgation of the mysteries rather than just their recognition; spectare seems to go better with ‘sacred rites’ than with ‘sacred objects’. This note therefore proposes tractare, comparing Petron. 83.1 and 140.13 besides Theocr. 26.7-14 and Clem. Alex. protrept. 21.2.